Shape‐Defined Hollow Structural Co‐MOF‐74 and Metal Nanoparticles@Co‐MOF‐74 Composite through a Transformation Strategy for Enhanced Photocatalysis Performance. Issue 35 (15th July 2019) - Deng, Xin; Yang, Lanlan; Huang, Hanlin; Yang, Yuying; Feng, Shiqiang; Zeng, Min; Li, Qi; Xu, Dongsheng
Abstract: In recent years, metal–organic frameworks (MOFs) have received extensive interest because of the diversity of their composition, structure, and function. To promote the MOFs' function and performance, the construction of hollow structural metal–organic frameworks and nanoparticle–MOF composites is significantly effective but remains a considerable challenge. In this article, a transformation strategy is developed to synthesize hollow structural Co‐MOF‐74 by solvothermal transformation of ZIF‐67. These Co‐MOF‐74 particles exhibit a double‐layer hollow shell structure without remarkable shape change compared to original ZIF‐67 particles. The formation of hollow structure stemmed from the density difference of Co between ZIF‐67 and Co‐MOF‐74. By this strategy, hollow structural Co‐MOF‐74 with different sizes and shapes are obtained from corresponding ZIF‐67, and metal nanoparticles@Co‐MOF‐74 is synthesized by corresponding nanoparticles@Co‐ZIF‐67. To verify the structural advantages of hollow structural Co‐MOF‐74 and Ag nanoparticles@Co‐MOF‐74, photocatalytic CO2 reduction is used as a model reaction. Conventionally synthesized Co‐MOF‐74 (MOF‐74‐C), hollow structural Co‐MOF‐74 synthesized by transformation method (MOF‐74‐T) and Ag nanoparticles@Co‐MOF‐74 (AgNPs@MOF‐74) are used as cocatalysts in this reaction. As a result, the cocatalytic activity of MOF‐74‐T and AgNPs@MOF‐74 is 1.8 times and 3.8 times that of MOF‐74‐C, respectively. Abstract : A novel transformation strategy is developed to synthesize hollow structural Co‐MOF‐74 with different sizes and shapes. In contrast to conventionally synthesized Co‐MOF‐74, hollow structural Co‐MOF‐74 (MOF‐74‐T) exhibits an obviously enhanced cocatalytic activity in a photocatalytic CO2 reduction system. Metal nanoparticles@Co‐MOF‐74 can also be synthesized by this strategy.